Arms and the Covenant, 1938 - Churchill, Winston S. (Early Speeches., 2013)
This inspiring collection of campaign speeches from the British Prime Minister bring his oratory brilliance and powers of persuasion to life. Legendary politician and military strategist Sir Winston Churchill was a master not only of the battlefield, but of the page and the podium. Over the course of forty books and countless speeches, broadcasts, news items and more, he addressed a country at war and at peace, thrilling with victory but uneasy with its shifting role on the global stage. In 1953, he was awarded the Nobel Prize for Literature for "his mastery of historical and biographical description as well as for brilliant oratory in defending exalted human values." During his lifetime, he enthralled readers and brought crowds roaring to their feet; in the years since his death, his masterful writing has inspired generations of eager history buffs. Well before Britain entered World War II, Winston Churchill warned his government about the growing Nazi threat, even as many European leaders were still urging caution and diplomacy. In this collection of forty-one speeches from 1928 to 1938, the great politician's prescience and political skill-vital to Britain's role as the first country to stand against Hitler-are clearly on display. This collection, which includes the famous "Disarmament Fable" speech, presents a fascinating look at Churchill's campaign to mobilize Britain against the rising Nazi threat, and showcases his versatility and genius as one of the best orators of the twentieth century.